Dynamics of local governance: The case of peatland restoration in Central Kalimantan, Indonesia. (March 2021) - Januar, Rizky; Sari, Eli Nur Nirmala; Putra, Surahman
Highlights: The implementation of restoration policy in Central Kalimantan involves cross-sectoral stakeholders. Despite some major advances in local peatland restoration, some challenges prevail. Current state of governance somewhat restricts the ability of restoration actors to adaptively address emerging challenges. Actions are suggested to further strengthen restoration process. Abstract: Since 2016, peatland restoration policy is implemented in Central Kalimantan province through facilitation and coordination by Peat Restoration Agency (Badan Restorasi Gambut [BRG]), with the goals of reducing the peat subsidence, greenhouse gas emissions, and vulnerability to fire of peat areas. After years of implementation, local peat fires persist, however, and knowledge is still lacking about the challenges and opportunities for supporting the restoration process. This study examines policy implementation from the perspective of regional stakeholders by unraveling the dynamics of stakeholder interactions associated with the policy process. It reveals that the current state of governance somewhat restricts the ability of restoration actors to adaptively address emerging policy challenges and proposes measures for addressing these challenges.